Reduction of Syndecan Transcript Levels in the Insulin-Producing Cells Affects Glucose Homeostasis in Adult Drosophila melanogaster. - Warren, J.L.; Hoxha, E.; Jumbo-Lucioni, P.; De Luca, M. (DNA, 2017)
Signaling by direct cell-matrix interactions has been shown to impact the transcription, secretion, and storage of insulin in mammalian ? cells. However, more research is still needed in this area. Syndecans are transmembrane heparan sulfate proteoglycans that function independently and in synergy with integrin-mediated signaling to mediate cell adhesion to the extracellular matrix. In this study, we used the model organism Drosophila melanogaster to determine whether knockdown of the Syndecan (Sdc) gene expression specifically in the insulin-producing cells (IPCs) might affect insulin-like peptide (ILP) production and secretion. IPCs of adult flies produce three ILPs (ILP2, ILP3, and ILP5), which have significant homology to mammalian insulin. We report that flies with reduced Sdc expression in the IPCs did not show any difference in the expression of ilp genes compared to controls. However, they had significantly reduced levels of the circulating ILP2 protein, higher circulating carbohydrates, and were less glucose tolerant than control flies. Finally, we found that IPCs-specific Sdc knockdown led to reduced levels of head Glucose transporter1 gene expression, extracellular signal-regulated kinase phosphorylation, and reactive oxygen species. Taken together, our findings suggest a cell autonomous role for Sdc in insulin release in D. melanogaster.